The race between tax enforcement and tax planning: Evidence from a natural experiment in Chile - Sebastian Bustos; Dina Pomeranz; Juan Carlos Suárez Serrato; José Vila-Belda; Gabriel Zucman (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Profit shifting by multinational corporations is thought to reduce tax revenue around the world. This paper provides a comprehensive analysis of the introduction of standard regulations to limit profit shifting. Using administrative tax and customs data from Chile, we find that the reform was ineffective in reducing multinationals' transfers to lower-tax countries and did not significantly raise tax payments. Interviews with tax advisors and employment history data reveal a drastic increase in consulting services. Our results illustrate that when enforcement can be circumvented by sophisticated tax planning, it can benefit tax consultants at the expense of tax authorities and taxpayers.
Keywords: H25; H26; H32; 330; Multinationales Unternehmen; Steuerplanung; Gewinnverlagerung; Unternehmensbesteuerung; Rechtsdurchsetzung; Experiment; Chile